Micellar promoted multi-component synthesis of 1, 2, 3-triazoles in water at room temperature. Issue 3 (26th January 2015) - Tasca, Elena; La Sorella, Giorgio; Sperni, Laura; Strukul, Giorgio; Scarso, Alessandro
Abstract : Micellar media in water provide a simple and efficient environment favoring the multi-component synthesis of 1, 2, 3-triazoles from organic bromides, sodium azide and terminal alkynes in the presence of [Cu(IMes)Cl]1 catalyst at room temperature within a few hours. Abstract : Micellar media in water provide a simple and efficient environment favoring the multi-component synthesis of 1, 2, 3-triazoles from organic bromides, sodium azide and terminal alkynes in the presence of [Cu(IMes)Cl]1 catalyst at room temperature within a few hours. The micellar medium favors both the in situ formation of the organic azide and its metal promoted cycloaddition with the alkyne.